The perceived benefits of and barriers to open-water swimming: A mixed-methods examination - Elliott, D.; Christie, M. A. (International Journal of Aquatic Research and Education, 2025)
This study set out to determine the perceived benefits of, and barriers to, open-water swimming (OWS). Adopting a mixed-methods approach, six hundred and sixty-five open-water swimmers responded to an online survey consisting of the Exercise Benefits and Barriers Scale (EBBS) and a series of open-ended questions. Data from the EBBS revealed the strongest perceived benefits to be `Psychological Outlook` and `Life Enhancement.` In terms of barriers, those presented in the EBBS received low ratings with only `Physical Exertion` considered as being somewhat problematic. Content analysis performed on the open-ended responses showed social aspects, mental well-being, and connection to nature as being particularly beneficial. Barriers to full participation included water pollution, accessibility, and poor weather conditions. These outcomes are discussed in relation to the uniqueness of the open-water swimming experience. Comparisons to other exercise modes also are presented.